Competencias digitales en docentes de las instituciones educativas del nivel inicial de Caballo Cocha, Ramón Castilla 2021 - Torres Simarri, Guida Marlena (2023)
The general objective of the research was to describe the level of digital competences in teachers of the Educational Institutions of the initial level of Caballo Cocha province of Ramón Castilla in the year 2021. As a research methodology the descriptive type was adopted, it had a cross-sectional field design and univariate. The population was made up of 16 initial level teachers, who also made up the sample. The data collection technique used was the survey and a questionnaire was used as an instrument, which was validated by experts on the subject. The main finding of the research is that the level of digital competences that the teachers of the initial level Public Educational Institutions of Caballo Cocha de Ramón Castilla show a low level in 10.9%, while 82.6% have a regular level and only 6.5% a high level. This result shows that it is necessary to improve the level of digital skills in the mentioned teachers.